STRUCTURE AND TYPES OF CONCEPTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
For a long time, researchers have been studying the ratio of components in one concept (or cultural phenomenon) and methods of their determination. It follows from the recognition of the concept with the content plan of the language sign that it contains all the information of communicative importance, except for the reference to the subject. First of all, it should be noted that the indicators of the position of this sign in the lexical system of the language are: its paradigmatic, syntagmatic and derivational links. The semantic content of the concept includes all pragmatic information related to the expressive and illocutionary functions of the linguistic sign. Another highly probable component of the semantics of the concept is the cognitive memory of the word: the semantic properties associated with the original purpose of the linguistic sign and the moral value system of native speakers. However, the most important here is the cultural and ethnic component, which determines the specific features of the semantics of natural language units and reflects the "linguistic picture of the world" of the speakers. I.A.Sternin emphasizes that the complex structure of the concept is related to its active dynamic role in the thinking process - it is always working, actualizing in its various components and aspects, connecting with other concepts and returning them. This is the meaning of thinking.